Operation Management Mode Based on New Media Technology - Peng Han (Dianxin kexue)
For tremendous impact has brought by the rapid development of the new media（such as Weibo，We-chat，micro video，e.g.）and the mobile internet，the difficulties the operators faced in the new media field and the way to deal with the challenges were analyzed.The methods and procedures for the new media analysis technique were proposed.The application of the new media technology in the marketing support analysis in several cases was elaborated.The function implementation of operational management and complaint management from the perspective of operational management were introduced，and then the system construction scheme and implementation effect for the new media operation and management system development were presented.